Potential of Pomelo Fruit (Citrus Maxima) Extract on T47D, WiDr, and HepG2 Cancer Cells - Vevi Maritha; Aris Hartono; Mega Arianti Putri (Journal of Global Pharma Technology, 2020)
Currently, alternative therapies are needed for breast, colon, and liver cancer patients. Those therapies are therapies that can selectively kill cancer cells without damaging other cells that have high development, such as hair and nails. One of those alternative therapies is the use of plants in cancer therapy. Pomelo has the potential as an anti-cancer agent because it contains phytochemical compounds, one of which is lycopene. Lycopene is a free anti-radical compound found in pomelo (citrus maxima). The lycopene content in pomelo fruit is more than in other parts, such as in leaves and fruit skin. Lycopene works by suppressing the proliferation or multiplication of cells through mutations in the initiation and progression phase of cancer. In cervical cancer patients, cell multiplication occurs quite rapidly, so that with the presence of lycopene, cervical cancer cell growth can be inhibited. Lycopene compounds can minimize the oxidation process and reduce the presence of free radicals in the body. Free radical compounds interact with DNA and reduce physiological functions that can increase cervical cancer cell growth. Lycopene is a compound that can counteract these free radicals and is also able to slow down or even prevent the oxidation process of other molecules and eliminate free radicals in the body that can cause cell damage. Through these two mechanisms, namely suppressing cell multiplication and eliminating free radicals, lycopene can be used as a cancer therapy. The cytotoxic activity test of pomelo fruit extract was carried out using the MTT method on T47D, WiDr, and HepG2 cells. The pomelo fruit was extracted by maceration method using 96% ethanol solvent. Cancer cell cultures were transferred as many as 1x104 cells/well in culture media consisting of FBS, penicillin-sterptomycin, amphoterizin-B, and RPMI 1640 into 96-well plates and incubated in a 5% CO2 incubator overnight. Furthermore, the test samples were given a series of levels and replications were made three times (triplo), and then they were incubated again overnight. On the third day of testing, MTT reagent was added, and after 4 hours, formazan crystals in living cells would be formed. Furthermore, SDS stoper was added to stop the MTT reaction. Then, the absorbance reading was carried out using an elisa reader at a wavelength of 595nm and the determination of the IC50 value was then carried out as well. The results showed that the IC50 value of pomelo extract in T47D 50 cells was 954.34 µg/mL, in WiDr cancer cells was 130.70 µg/mL, and in HepG2 cancer cells was 1,660.257 µg / mL. This shows that pomelo extract has the potential as an anti-cancer agent for breast and colon cancer, but not for liver cancer. This research could contribute to the development of breast and colon cancer drugs.